A comparison of sacral neuromodulation vs. transvaginal electrical stimulation for the treatment of refractory overactive bladder: the impact on quality of life, body image, sexual function, and emotional well-being - La Rosa, Valentina Lucia; Platania, Alessio; Ciebiera, Michał; Garzon, Simone; Jędra, Robert; Ponta, Marco; Butticè, Salvatore (Menopause Review/Przegląd Menopauzalny, 2019)
Overactive bladder syndrome (OAB) is defined by the presence of urinary urgency, with or without urge incontinence, usually accompanied by an increase in urinary frequency and nocturia in the absence of urinary tract infections (UTI) or other diseases. The overall prevalence of OAB symptoms in the female population is reported to be 16.6% and increases with advancing age and menopause. The aetiology of OAB is not fully understood and is likely to affect a heterogeneous population of patients due to changes to their central and peripheral nervous systems. Although OAB is frequently associated with female sexual dysfunction (FSD), its real impact on sexual function in women has been evaluated only in a few studies. The first line of treatment for OAB includes behavioural modification and physical therapy, either as monotherapies or in combination. Many patients who have not had success in managing their symptoms with more conservative therapies may decide to resort to third-line treatments for refractory OAB. These treatments include neuromodulation therapies, particularly transvaginal electrical stimulation (TES) and sacral neuromodulation (SN). The aim of this short commentary is to provide an overview of the effectiveness of these treatments and of their impact on quality of life, body image, sexual function, and emotional well-being.